Matrix metalloproteinase-driven epithelial-mesenchymal transition: implications in health and disease - Ghazaleh Khalili-Tanha; Evette S. Radisky; Derek C. Radisky; Alireza Shoari (Journal of Translational Medicine)
Abstract Epithelial–mesenchymal transition (EMT) is a process in which epithelial cells, defined by apical–basal polarity and tight intercellular junctions, acquire migratory and invasive properties characteristic of mesenchymal cells. Under normal conditions, EMT directs essential morphogenetic events in embryogenesis and supports tissue repair. When dysregulated, EMT contributes to pathological processes such as organ fibrosis, chronic inflammation, and cancer progression and metastasis. Matrix metalloproteinases (MMPs)—a family of zinc-dependent proteases that degrade structural components of the extracellular matrix—sit at the nexus of this transition by dismantling basement membranes, activating pro-EMT signaling pathways, and cleaving adhesion molecules. When normally regulated, MMPs promote balanced ECM turnover and support the cyclical remodeling necessary for proper development, wound healing, and tissue homeostasis. When abnormally regulated, MMPs drive excessive ECM turnover, thereby promoting EMT-related pathologies, including tumor progression and fibrotic disease. This review provides an integrated overview of the molecular mechanisms by which MMPs both initiate and sustain EMT under physiological and disease conditions. It discusses how MMPs can potentiate EMT through TGF-β and Wnt/β-catenin signaling, disrupt cell–cell junction proteins, and potentiate the action of hypoxia-inducible factors in the tumor microenvironment. It discusses how these pathologic processes remodel tissues during fibrosis, and fuel cancer cell invasion, metastasis, and resistance to therapy. Finally, the review explores emerging therapeutic strategies that selectively target MMPs and EMT, ranging from CRISPR/Cas-mediated interventions to engineered tissue inhibitors of metalloproteinases (TIMPs), and demonstrates how such approaches may suppress pathological EMT without compromising its indispensable roles in normal biology.